Phase‐Selective Syntheses of Cobalt Telluride Nanofleeces for Efficient Oxygen Evolution Catalysts. (1st June 2017) - Gao, Qiang; Huang, Chuan‐Qi; Ju, Yi‐Ming; Gao, Min‐Rui; Liu, Jian‐Wei; An, Duo; Cui, Chun‐Hua; Zheng, Ya‐Rong; Li, Wei‐Xue; Yu, Shu‐Hong
Abstract: Cobalt‐based nanomaterials have been intensively explored as promising noble‐metal‐free oxygen evolution reaction (OER) electrocatalysts. Herein, we report phase‐selective syntheses of novel hierarchical CoTe2 and CoTe nanofleeces for efficient OER catalysts. The CoTe2 nanofleeces exhibited excellent electrocatalytic activity and stablity for OER in alkaline media. The CoTe2 catalyst exhibited superior OER activity compared to the CoTe catalyst, which is comparable to the state‐of‐the‐art RuO2 catalyst. Density functional theory calculations showed that the binding strength and lateral interaction of the reaction intermediates on CoTe2 and CoTe are essential for determining the overpotential required under different conditions. This study provides valuable insights for the rational design of noble‐metal‐free OER catalysts with high performance and low cost by use of Co‐based chalcogenides.